Q-switched thulium/holmium fiber laser with gallium selenide - Ahmad, Harith; Reduan, Siti Aisyah; Sharbirin, Anir Syazwan; Ismail, Mohammad Faizal; Zulkifli, Mohd Zamani (Elsevier, 2018)
A passively Q-switched thulium/holmium fiber laser with a gallium selenide (GaSe) saturable absorber (SA) is proposed and demonstrated for the first time. The GaSe based SA is prepared by mechanical exfoliation and inserted into the proposed laser cavity to generate Q-switched pulses. Stable Q-switching operation is achieved at 1986.0 nm, with output pulse repetition rates ranging from 22.9 kHz to 32.3 kHz over a pump power range of 112.0 mW to 235.0 mW. The generated Q-switched pulses have a maximum pulse energy of 120.3 nJ and minimum pulse width of 6.9 μs. The proposed thulium/holmium fiber laser with GaSe SA will be able to cater to multiple applications requiring pulsed laser outputs in the 2.0 μm region.